2020
DOI: 10.3390/ijms21165883
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electronegative LDL with Macrophage Foam Cell Formation and CD11c Expression in Rheumatoid Arthritis Patients

Abstract: L5, the most negatively charged subfraction of low-density lipoprotein (LDL), is implicated in atherogenesis, but the pathogenic association is relatively unexplored in patients with rheumatoid arthritis (RA). We examined the role of L5 LDL in macrophage foam cell formation and the association of L5 with CD11c expression in THP-1 cells and RA patients. Using quantitative real-time PCR, we determined mRNA expression levels of ITGAX, the gene for CD11c, a marker associated with vascular plaque formation and M1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In three comprehensive studies, researchers have recently shown that circulating L5 levels are significantly increased in patients with RA or SLE whose plasma LDL-C levels are equal to or lower than those of healthy control individuals [ 56 , 57 , 86 ]. In a cohort of patients with RA, the plasma L5% and L5 concentration were significantly higher in those with subclinical atherosclerosis than in those without it, despite similar LDL-C levels among all the study participants [ 56 ].…”
Section: Electronegative Ldl and Its Atherogenicitymentioning
confidence: 99%
See 3 more Smart Citations
“…In three comprehensive studies, researchers have recently shown that circulating L5 levels are significantly increased in patients with RA or SLE whose plasma LDL-C levels are equal to or lower than those of healthy control individuals [ 56 , 57 , 86 ]. In a cohort of patients with RA, the plasma L5% and L5 concentration were significantly higher in those with subclinical atherosclerosis than in those without it, despite similar LDL-C levels among all the study participants [ 56 ].…”
Section: Electronegative Ldl and Its Atherogenicitymentioning
confidence: 99%
“…The plasma L5% and L5 concentration were also positively correlated with the extent of carotid artery atherosclerosis reflected by the intima–media thickness (IMT), disease activity score, and 10-year ASCVD risk score [ 56 ]. Further investigation revealed that L5 contributes to atherogenesis by augmenting macrophage foam cell formation, upregulating integrin CD11c expression, and enhancing inflammatory mediators including IL-6, IL-8, and tumor necrosis factor (TNF)-α [ 86 ]. These findings provide a mechanistic link between L5 and ASCVD development and clinical manifestations [ 56 , 57 , 79 , 86 ].…”
Section: Electronegative Ldl and Its Atherogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The study researchers discuss the significance of the immune system reaction to a foreign antigen and the impact on inflammatory cells in OA [12]. Chang and colleagues describe findings suggesting that electronegative low-density lipoprotein (LDL) may promote atherogenesis by augmenting macrophage foam cell formation, upregulating CD11c expression, and enhancing the expression levels of atherosclerosis-related mediators in RA [13]. In another study, Hähnlein and colleagues discuss evidence suggesting that human lymph node stromal cells (LNSCs) from RA patients regulate peripheral tolerance, making these cells a novel target to exploit in tolerance maintenance and induction [14].…”
mentioning
confidence: 99%